2021
DOI: 10.3390/met11020275
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Precipitation in 7055 Aluminum Alloy by Laser Ultrasonics

Abstract: After different rolling conditions, four 7055 aluminum alloy samples with different precipitation sizes were measured by scanning electron microscope, transmission electron microscope and laser ultrasonic. The attenuation coefficients of ultrasound measured by laser ultrasonic were calculated in the time domain, frequency domain and wavelet denoising, respectively. The relationship between the precipitate size and attenuation coefficient was established. The results show that the attenuation of the ultrasonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…The SEM images obtained from the fracture zone of the stainless steel samples showed a predominantly brittle fracture, as can be seen in Figure 9 c,d, with more cracking zones and pores than the aluminum sample. Similar data were reported in [ 38 , 39 , 40 , 41 , 42 , 43 ]. In the case of the stainless steel samples, it was observed that the fracture angle between the applied traction load axis and the fracture surface was almost perpendicular and showed a relatively flat fracture surface, as seen in Figure 9 b.…”
Section: Resultssupporting
confidence: 90%
“…The SEM images obtained from the fracture zone of the stainless steel samples showed a predominantly brittle fracture, as can be seen in Figure 9 c,d, with more cracking zones and pores than the aluminum sample. Similar data were reported in [ 38 , 39 , 40 , 41 , 42 , 43 ]. In the case of the stainless steel samples, it was observed that the fracture angle between the applied traction load axis and the fracture surface was almost perpendicular and showed a relatively flat fracture surface, as seen in Figure 9 b.…”
Section: Resultssupporting
confidence: 90%
“…Movahedirad et al [22] studied the influence of the ultrasonic vibration input containing the parabolic logarithm term on the flow field and obtained a more realistic flow field state. Combining with the relevant ultrasonic decay formula and the magnitude of the coefficient [28] , [29] , it is assumed that the upper boundary ultrasonic input is exponential decay symmetrical along the center, and the boundary condition is: …”
Section: Numerical Methods and Proceduresmentioning
confidence: 99%
“…In polycrystalline materials, these occur primarily at grain boundaries. Thus, in metallic materials such as aluminum alloys, conclusions can be drawn about grain size changes due to absorption [17] and precipitation effects due to velocity variation [18].…”
Section: Non-destructive Contact-free Measurement Techniquementioning
confidence: 99%